ANALISA PENGARUH JARAK CHOKE BEAN TERHADAP LAJU EROSI ALIRAN DUA FASA STEAM-SOLID DI DALAM ELBOW PADA PIPA VERTIKAL INJEKTOR UAP PT. CHEVRON PACIFIC INDONESIA (CPI) MENGGUNAKAN CFD - Abrorul Fuady R.; MSK. Tony SU.; Eflita Yohana (JURNAL TEKNIK MESIN, 2013)
Choke bean is essentially needed on hydrocarbon production system. The main function of this tool is to restrain and regulate flow rate of fluids in the pipe through a hole of the choke bean known as orifice. The use of the choke bean is very risky because of the relatively high velocity fluid that comes out of the choke due to the narrowing of the flow. High velocity may cause huge turbulence which affects the rate of erosion in the elbow. The purpose of this study is to determine the effect of distance variations of the choke bean with the elbow; and velocity of the fluid toward the erosion rate in the elbow using CFD. Distance variations of the choke bean  with elbow  are 12 in (0,3048 m), 24 in (0,6096 m)  and 36 in (0,9144 m) . Variations of the fluid velocity are 15,99 m/s, 22,39 m/s and 28,78 m/s. Simulation results shows that the greater the distance between the choke bean with the elbow causes a decrease in the erosion rate. The increased fluid velocity affects to the increasing the erosion rate.